Elucidating the role of MMP9 in hyperhomocysteinemia induced degradation of the neurovascular unit. (20th December 2022) - Gearon, Mary D; Early, Alexandria N; Weekman, Erica M; Lee, Tiffany; Wilcock, Donna M
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) is one of the leading causes of dementia. Hyperhomocysteinemia has been identified as a risk factor for VCID though the mechanism behind this connection has yet to be determined. Hyperhomocysteinemia increases inflammation inducing the upregulation of matrix metalloproteinase 9 (MMP9) activity. MMP9 has been shown to degrade several substrates along the neurovascular unit including claudin 5, collagen 4, occludin and β‐dystroglycan. I hypothesize that increased MMP9 activity following the induction of hyperhomocysteinemia leads to the cleavage of important anchoring proteins along the neurovascular unit weakening the integrity of the blood brain barrier which contributes to the progression of VCID pathology. Method: C57BL6 WT and MMP9 knockout mice were placed on a control diet or a diet deficient in vitamins B6, B12 and folate and enriched in methionine to induce hyperhomocysteinemia for 4, 8, 12 and 16 weeks. Western blot analysis was performed to investigate the substrates of MMP9 including claudin, occludin, and β‐dystroglycan. Result: Studies are underway to examine if MMP9 activation contributes to blood brain barrier dysfunction directly by degrading tight junction proteins leading to a weakened endothelial cell barrier and/or indirectly by cleaving proteins responsible for maintaining the connection between astrocytic end feet and the endothelial basement membrane. Conclusion: Our findings suggest that increased levels of MMP9 activity may impact several aspects of the neurovascular unit to contribute to VCID pathology. Further investigations focused on inhibition of MMP9 activation could provide the field with an important target for mitigating progression of this disease.